2021
DOI: 10.1002/jpln.202100295
|View full text |Cite|
|
Sign up to set email alerts
|

Biogeochemical limitations of carbon stabilization in forest subsoils#

Abstract: Background Soils are important carbon (C) sinks or sources and thus of utmost importance for global carbon cycling. Particularly, subsoils are considered to have a high potential for additional C storage due to mineral surfaces still available for sorptive stabilization. Aims Little information exists about the extent to which additional litter‐derived C is transferred to and stabilized in subsoils. This study aimed at evaluating the role of litter‐derived dissolved organic matter (DOM) inputs for the formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…It is unclear how these observations interact with different soil environmental conditions and profile characteristics to govern SOC dynamics over timescales meaningful for SOC stock changes. Liebmann et al (2022) indicated that surface litter derived-C does not strongly contribute to SOC stabilization in a temperate forest subsoil. They also concluded that the role of forest subsoils as a future C sink needs further consideration.…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…It is unclear how these observations interact with different soil environmental conditions and profile characteristics to govern SOC dynamics over timescales meaningful for SOC stock changes. Liebmann et al (2022) indicated that surface litter derived-C does not strongly contribute to SOC stabilization in a temperate forest subsoil. They also concluded that the role of forest subsoils as a future C sink needs further consideration.…”
mentioning
confidence: 96%
“…
Liebmann et al (2022) unveiled some of the biogeochemical mechanisms that can restrict the stabilization of litter-derived carbon (C) as soil organic carbon (SOC) in subsoils beneath a temperate beech (Fagus sylvatica L.) forest. We applaud the multi-pronged approach the authors invoked to track the potential fate of aboveground C in subsoils.
…”
mentioning
confidence: 99%
See 3 more Smart Citations